PERENCANAAN SISTEM INFORMASI TERINTEGRASI DI KONVEKSI MARIEE MENGGUNAKAN GOOGLE SHEETS DALAM MEMFASILITASI KOMUNIKASI ANTAR BAGIAN - Wira Yoganata, Maheswara; Satrio Irawan, Fandy; Evi Yuliana, Margaretha (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
Type This research aims to explore the use of Google Sheets as a communication tool in the context of integrated information systems at Mariee Konveksi. The data collected identified communication barriers between sections within the company, including suboptimal response times and delays in the availability of information needed by various sections. This research adopted a qualitative approach and took a descriptive form, involving staff from various sections at Mariee Convection who used Google Sheets as a data reporting tool. Careful planning for the use of Google Sheets is key in ensuring the smooth running of the integrated information system. This research explores the features and benefits of Google Sheets as a collaboration and data reporting tool. The results show that real-time data changes enable quick and accurate data access by various departments, improving internal communication and operational efficiency. As such, this research presents an important contribution to the understanding of how the use of up-to-date technology such as Google Sheets can improve a company's productivity and competitiveness, with a positive impact on faster product delivery, higher levels of customer satisfaction, and sustainable growth for Mariee Convection.